The Effectiveness of Rational Emotional Counseling Program in Reducing the Depressive Symptoms Among Retired Individuals in Salfeet Governorate - Belbeisi, Mona AbdelQader; Ibrahim, Alaa Abdel Hakim (Journal of Educational and Psychological Sciences, 2025)
Objectives: This study aimed to assess the effectiveness of a rational emotional counseling program in reducing depressive symptoms among retired individuals in Salfeet Governorate.Methods: The study included 30 retired individuals with high depressive symptom scores, divided into experimental and control groups (15 each). A researcher-developed depressive symptoms scale, validated for the Palestinian environment, was used. An 11-session, 60-minute rational emotional counseling program was applied to the experimental group. According to the quasi-experimental approach.Results: While no significant pre-program differences were found between groups, the experimental group showed statistically significant reductions in depressive symptoms after the program compared to the control group. Furthermore, the experimental group's depressive symptom scores significantly decreased from pre-program to post-program measurements and maintained these reductions at follow-up.Conclusions: Key recommendations include using audio-visual media to educate Palestinian society about depressive disorders through various public engagements. Additionally, developing group treatment plans that foster interaction among retirees, in collaboration with psychological counseling centers and mental health departments, is crucial for alleviating psychological distress.
Keywords: Rational Emotional Counseling Program; Depressive Symptoms; Retired Individuals in Salfeet Governorate